Decentralisation and local government autonomy in Southeast Asia - Harding, Andrew James (Đại học Quốc Gia Hà Nội, 2020)
Since the early 1990s there has occurred a largely unsung drive towards decentralisation across most of the world, including Southeast Asia. Decentralisation has conferred autonomy on regional or provincial, and (the major focus of this study) local government authorities. Democratic elections have proliferated at the subnational level, extending the reach of democracy and constitutional government. Over three decades decentralisation has indeed become ubiquitous at a global level. In virtually every country, subnational autonomy extending to local government has increased, and in many cases this development has been constitutionally sanctioned or mandated. As this book will show, Southeast Asia has decentralised the nation-state to a degree that is quite surprising, given the region’s reputation for creating authoritarian, illiberal states. Africa, South Asia and South America, too, as ‘developing areas’, have seen a good deal of decentralisation, reflected even more obviously in the literature than Asian stories of decentralisation. The more prosperous, and generally longer-established, states of Europe and North America have also seen a measure of, or at least a demand for, decentralisation, even though their systems of territorial governance were initially established many decades ago. These systems have in turn influenced the design of territorial governance in countries that were colonised by them. Devolution of powers and ‘regionalism’ in Europe represent obvious, more recent, examples of decentralisation